Both Medialization and Anteromedialization Tibial Tubercle Osteotomies are Effective Surgical Management for Skeletally Mature Patients with Patellofemoral Instability when Combined with Medial Patellofemoral Ligament Reconstruction - Tan, Si Heng Sharon; Aw, Angeline Ai Ling; Goh, Xin Chun Amelia; Tan, Luke Yi Hao; Lim, Andrew Kean Seng; Hui, James Hoipo (The Journal of Knee Surgery, 2022)
The study aimed to compare the midterm outcomes of medialization and anteromedialization tibial tubercle osteotomies when used in the management of recurrent patellofemoral instability. The hypothesis is that both techniques would result in significant improvement for patellofemoral instability, but anteromedialization would result in a lower incidence of early osteoarthritis. In the cohort study, all skeletally mature patients aged 18 years old or younger who underwent tibial tubercle osteotomy for recurrent patellofemoral instability within a 10-year period in a single institution were included. All patients underwent either medialization or anteromedialization tibial tubercle osteotomy. The preoperative and postoperative outcomes of the tibial tubercle osteotomies were compared. All patients included in the study had a minimum of 5-year follow-up duration before the conclusion of the study. There was no statistically significant difference in the rates of preoperative and postoperative patellofemoral dislocation when either technique was employed (p = 0.999). Additionally, both the preoperative and postoperative Kujala scores were similar (p = 0.166 and p = 0.554, respectively). The knees did not have a statistically significant difference in their patellar tilt angles and tibial tubercle-trochlear groove distances preoperatively or postoperatively when either technique was used (p = 0.165 and 0.149, respectively). There was also no incidence of osteoarthritis identified in either of the groups (p = 0.999). Both anteriorization and anteromedialization tibial tubercle osteotomies were effective surgical management for patellofemoral instability when combined with medial patellofemoral ligament reconstruction. There were no significant differences in clinical, functional, and radiological outcomes when either medialization or anteromedialization tibial tubercle osteotomy was performed.
Keywords: tibial tubercle osteotomy; tibial tuberosity osteotomy; tibial tubercle medialisation; tibial tubercle anteromedialisation